Comparison of angle stable plate fixation approaches for distal radius fractures - Matschke, Stefan; Wentzensen, Andreas; Ring, D.; Marent-Huber, M.; Audigé, L.; Jupiter, J. B. (Injury, 2011)
Introduction - The aim of the study was to compare radiological and functional outcomes between volar and dorsal surgical fixation of distal radius fractures using low-profile, fixed-angle implants. - Patients and methods - A total of 305 distal radius fracture patients were treated with Synthes locking compression plate (LCP) 2.4- or 3.5-mm fixation using either a volar (n=266) or dorsal (n=39) approach. The patients were examined at 6 months, 1 and 2 years for radiological assessment of fracture healing, alignment, reduction and arthritis, as well as the determination of various functional outcome scores. - Results - Both groups were comparable with respect to baseline and injury characteristics. The complication rate was higher for the volar approach (15%). No significant differences were observed for Disabilities of the Arm, Shoulder and Hand (DASH) and Short Form (36) Health Survey (SF-36) scores, pain, arthritis grade, grip strength and radiological measurements. However, a significantly better functional outcome represented by a low mean Gartland and Werley score was observed for the volar approach after 6 and 12 months. Significantly higher percentages of dorsal extension, palmar flexion, ulnar deviation and supination angle (relative to the mean contralateral healthy wrist) were also reported for volar approach patients at the 6-month follow-up. - Conclusions - Volar internal fixation of distal radius fractures with LCP DR implants can result in earlier and better functional outcome compared with the dorsal approach, yet is associated with a higher incidence of complications. After 2 years, these differences are no longer observed between the two surgical methods.